The new home : a handbook for tenants (London : The Health and Cleanliness Council, 1937)
1937 1937 1930s 24 pages : illustrations HOT WATER IS AN ESSENTIAL OF CLEANLINESS Hot water is a real blessing, especially if there are children in the house. Modern electric equipment will boil water at any time without smoke or fumes, which may be dangerous to health. [illustration] An electric water-heater. PORTABLE ELECTRIC FIRES SAVE MONEY IN THE END By these you can carry the warmth where it is most wanted, instead of making and keeping several fires. See that the electric fires have guards fixed to them. [illustration] Fix fire guards. ON FURNITURE AND FURNISHING Don't have any unnecessary furniture in a room. It makes the work of cleaning more difficult, takes up too much space, and gives an impression of stuffiness. Furniture has to be kept clean and polished, and it is labour-saving to get rid of what is not in use. Don't allow a piece of furniture to remain unless there is a good reason for keeping it. DON'T PUT DIRT AWAY IN YOUR CUPBOARDS Built-in cupboards and wardrobes should be turned out and scrubbed regularly with soap and water and allowed to dry. Built-in cupboards though more dust-proof are less well-aired than movable furniture and must not be neglected. If you have an electric vacuum cleaner, use it to suck out dirt and dust from the corners and ledges. [illustration] Save space. 5 177/5/8/2